On sustainable land rent - Özdilek, Ünsal (Frontiers in Sustainability, 2024)
This paper introduces the concept of Sustainable Land Rent (SLR), providing a comprehensive, multidimensional exploration anchored in the dynamics of its origin, separability, mobility, valuation, and the imperative for equitable distribution. SLR capitalizes on the economic mobility of land's value to enhance community welfare and promote environmental sustainability. Advocating for the systematic institutionalization of SLR, the research tackles the complex challenge of distinguishing land value from improvements. Employing traditional Price, Cost, and Income (PCI) methods as practiced in North America, the study addresses the technical challenge of inseparability by estimating and integrating the SLR value within each of these methods. The methodology clarifies the valuation process and establishes an objective framework for resource allocation and negotiation between public and private sectors. Furthermore, our findings highlight SLR's vital role in advancing public revenue generation and underscore its function as an innovative catalyst for integrating sustainability into economic valuation models and practices in real estate development and urbanization.